2024
DOI: 10.1186/s12859-023-05621-5
|View full text |Cite
|
Sign up to set email alerts
|

Deep evolutionary fusion neural network: a new prediction standard for infectious disease incidence rates

Tianhua Yao,
Xicheng Chen,
Haojia Wang
et al.

Abstract: Background Previously, many methods have been used to predict the incidence trends of infectious diseases. There are numerous methods for predicting the incidence trends of infectious diseases, and they have exhibited varying degrees of success. However, there are a lack of prediction benchmarks that integrate linear and nonlinear methods and effectively use internet data. The aim of this paper is to develop a prediction model of the incidence rate of infectious diseases that integrates multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Recently, an LSTM model predicted clinical factors and treatment outcomes [ 10 , 11 ]. In the same vein, the autoregressive moving average (ARIMA) and the seasonal ARIMA (SARIMA) models provide another predictive approach to time series forecasting of the spreading of various infectious diseases [ 12 , 13 ]. The results showed that combination models were better than single ARIMA models [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an LSTM model predicted clinical factors and treatment outcomes [ 10 , 11 ]. In the same vein, the autoregressive moving average (ARIMA) and the seasonal ARIMA (SARIMA) models provide another predictive approach to time series forecasting of the spreading of various infectious diseases [ 12 , 13 ]. The results showed that combination models were better than single ARIMA models [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%